Economic and ethical challenges of "land grabs" in sub-Saharan Africa - Linda Kleemann; Jann Lay; Kerstin Nolte; Konrad Ott; Rainer Thiele; Lieske Voget-Kleschin (Kiel Institute for the World Economy (IfW), 2013)
For local people in sub-Saharan Africa, large land investment projects currently imply many risks and few benefits. Drawing on own ethical and economic research and using evidence from the authors' case studies in Kenya, Mali and Zambia and a new database of large-scale land acquisitions worldwide, this brief offers policy recommendations for host governments, investors and the international community so as to achieve a more favourable balance of risks and benefits in land investment projects. Our research suggests that the land governance systems of sub-Saharan African countries, comprising a multitude of sometimes contradictory laws derived from colonial and customary systems, privilege powerful actors and lead to violation of human rights. Legal uncertainty and an acquisition process that gives no voice to local land users can lead to displacements of farmers without compensation. Poorly enforced formal laws, neglect of built-in checks and balances, and power and information asymmetries between investors and local people can give rise to coalitions of investors and powerful rent-seekers. Displaced farmers and those unable to find jobs on the land investment projects migrate to other rural areas or the cities, and few and only low-skilled jobs are available to those who remain. We found limited evidence of positive spillovers from improved infrastructure and knowledge and technology transfer. Local food prices are likely to rise, as most of the production on investment farms is for export. Overall, when many farmers are displaced and investment projects are capital intensive the net welfare effect for the local population can be expected to be negative. Against this background, we propose a set of policy changes for promoting benefits for the local population and avoiding human rights violations. In contrast to proposals made by international guidelines and codes of conduct, we emphasize in particular the responsibilities of host country governments.
Keywords: 330